Предмети з кургану Огуз в колекції В. Н. та Б. І. Ханенків (за матеріалами Музею історичних коштовностей України) - Величко, Є.О.; Полідович, Ю.Б. (Археологія і давня історія України, 2021)
У статті проаналізовано коштовні предмети з колекції В. Н. та Б. І. Х аненків, що мовбито походять з кургану Огуз. Робиться висновок про беззаперечне походження з Огузу тільки предметів оздоблення кінського спорядження. Значну частину інших предметів (оббивку дерев’яної чаші, прикраси, пластини-аплікації), вірогідно, знайдено в інших степових курганах, а, можливо, й в некрополях античних міст, пограбованих копачами на початку ХХ ст. Twenty six precious items from the Varvara and Bohdan Khanenko collection discovered in the Oguz kurgan (Lower Dnieper region) are analyzed in the paper. These items were found by peasants in the fall of 1901 in the destroyed part of the kurgan and ended up to the hands of antiquities traders. Now these items are kept in the Museum of Historical Treasures of Ukraine. The study of objects made us possible to conclude that only decorative items for horse equipment were of unconditional origin from Oguz kurgan (fig. 1—2). These items complement the finds that are kept in the State Hermitage (Sankt-Peterburg, Russia) and also come from the Oguz kurgan. Together they are four completes sets of decoration of horse bridle of so-called Chertomlyk type. Some round plaques (fig. 1: 4—5) were used for saddles decoration. The total number of such plaques indicates that 9 or 10 saddles were found. This determines the total number of horses buried in the Central tomb of the Oguz kurgan. The cone (fig. 2) served as a decoration for the horse’s neck. Five more such items are kept in the State Hermitage. They were found only in the Oguz kurgan. The significant part of other items (upholstery of a wooden bowl, jewelry, appliquйs (fig. 3) were probably found by peasants in other steppe kurgans which were robbed by diggers at the beginning of the 20th century. Two small appliquйs (fig. 3: 5—6) probably come from the necropolises of ancient Greek colonies, possibly Chersonesos. Unfortunately, almost all items from old or modern private collections lose the historical context in which they were found. Probably, some items (fig. 1: 6—9; 3: 3—4, 7—8) were «restored» by antiquities dealers and, as a result, lost their authentic appearance.